(untitled) - United States; Federal Trade Commission (Washington, 1952)
Resources and concentration of the World petroleum industry; Development of joint control over the international petroleum industry; production and marketing agreements.
Keywords: Petroleum industry and trade,Ngành công nghiệp dầu mỏ và thương mại